Advance care planning among Medicare beneficiaries with dementia undergoing surgery. Issue 8 (20th May 2021) - Shah, Samir K.; Manful, Adoma; Reich, Amanda J.; Semco, Robert S.; Tjia, Jennifer; Ladin, Keren; Weissman, Joel S.
Abstract: Importance: Advance care planning (ACP), in which patients or their surrogates discuss goals and preferences for care with physicians, attorneys, friends, and family, is an important approach to help align goals with actual treatment. ACP may be particularly valuable in patients with advanced serious illnesses such as Alzheimer's disease and related dementias (ADRDs) for whom surgery carries significant risks. Objective: To determine the frequency, timing, and factors associated with ACP billing in Medicare beneficiaries with ADRD undergoing nontrauma inpatient surgery. Design: This national cohort study analyzes Medicare fee‐for‐service claims data from 2016 to 2017. All patients had a 6‐month lookback and follow‐up period. Setting: National Medicare fee‐for‐service data. Participants: All patients with ADRD, defined according to the Chronic Conditions Warehouse, undergoing inpatient surgery from July 1, 2016 to June 30, 2017. Exposures: Patient demographics, medical history, and procedural outcomes. Main Outcome: ACP billing codes from 6 months before to 6 months after admission for inpatient surgery. Results: This study included 289, 428 patients with ADRD undergoing surgery, of whom 21, 754 (7.5%) had billed ACP within the 6 months before and after surgical admission. In a multivariable analysis, patients of white race, male sex, and residence in the Southern and Midwestern United States were at the highest risk of not receiving ACP. Of all patients who received ACP, 5960 (27.4%) did so before surgery while 12, 658 (52.8%) received ACP after surgery. Timing of ACP after surgery was associated with an Elixhauser comorbidity index of 3 or higher (1.23, p = 0.045) and major postoperative complication or death (odds ratio 1.52, p < 0.0001). Conclusions and Relevance: Overall ACP billing code use is low among Medicare patients with ADRD undergoing surgery. Billed ACP appears to have a reactive pattern, occurring most commonly after surgery and in association with postoperative mortality and complications. Additional study is warranted to understand barriers to use.